Information and communications technology use to prevent and respond to sexual and gender‐based violence in low‐ and middle‐income countries: An evidence and gap map. Issue 4 (25th October 2022) - Philbrick, William; Milnor, Jacob; Deshmukh, Madhu; Mechael, Patricia
Abstract: Background: The use of information and communications technologies (ICT) in low‐ and middle‐income countries (LMIC) has increased significantly in the last several years, particularly in health, including related areas such as preventing and responding to sexual and gender‐based violence (SGBV) against women and children. While the evidence for ICT effectiveness has grown significantly in the past 5 years in other aspects of health, it has not for effectiveness of using ICT for the prevention and response to SGBV against women and children in LMIC. Objectives: The primary goal of this evidence and gap map (EGM) is to establish a baseline for the state of the evidence connected with the use of ICT for preventing and responding to SGBV against women and children in LMIC. Objectives that contribute to the achievement of this goal are: (1) identifying evidence of effectiveness for the use of ICT targeting the prevention of, and response to, SGBV against women and children in LMIC; (2) identifying key gaps in the available ICT for SGBV prevention and/or response evidence; (3) identifying research methodology issues reflected in the current evidence; (4) identifying any clusters of evidence in one or more ICT interventions suitable for systematic review; (5) identifying enabling factors associated with effective interventions using ICT for the prevention of, and response to, SGBV against women and children in LMIC; and (6) providing a structured and accessible guide to stakeholders for future investment into interventions and research using ICT for SGBV prevention and response in LMIC. Search Methods: The date of the last search from which records were evaluated, and any studies identified were incorporated into the EGM was July 11, 2021. Twenty (20) databases were searched, and identified under "Methods." Selection Criteria: We conducted systematic searches of multiple academic databases using search terms and criteria related to the use of ICT for prevention and/or response to SGBV against women and children. Although excluded, we did consider studies conducted in higher‐income countries (HIC) only to provide context and contrast for the EGM discussion of the eligible studies from LMIC. Data Collection and Analysis: The EGM search process included five phases: (1) initial search of academic databases conducted by two researchers simultaneously; (2) comparison of search results, and abstract screening by two researchers collaboratively; (3) second screening by reviewing full articles of the studies identified in the first screening by two reviewers independently; (4) comparison of results of second screening; resolution of discrepancies of screening results; and (5) data extraction and analysis. Main Results: The EGM includes 10 studies published in English of which 4 were systematic, literature or scoping reviews directly addressing some aspect of the use of ICT for SGBV prevention and/or response in women and girls. The six individual studies were, or are being, conducted in LMIC (a condition for eligibility). No eligible studies addressed children as a target group, although a number of the ineligible studies reported on the use of ICT for intermediate outcomes connected with violence against children (e.g., digital parenting). Yet, such studies did not explicitly attach those intermediate outcomes to SGBV prevention or response outcomes. Countries represented among the eligible individual studies include Cambodia, Kenya, Nepal Democratic Republic of Congo (DRC), and Lebanon. Of the 10 eligible studies (individual and reviews), most focused on intimate partner violence against women (IPV). Intervention areas among the eligible studies include safety planning using decision algorithms, educational and empowerment messaging regarding norms and attitudes towards gender‐based violence (GBV), multi‐media radio drama for social behavior change, the collection of survivor experience to inform SGBV/GBV services, and the collection of forensic evidence connected to the perpetration of SGBV. Thirty‐one studies which otherwise would have been eligible for the evidence and gap map (EGM) were conducted in HIC (identified under "Excluded Reviews"). None of the eligible studies reported results related to effectiveness of using ICT in a control setting, for the primary prevention of SGBV as an outcome, but rather reported on outcomes such as usability, secondary and tertiary prevention, feasibility, access to services and other outcomes primarily relating to the development of the interventions. Two studies identified IPV prevention as a measurable outcome within their protocols, but one of these had not yet formally published results regarding primary prevention as an outcome. The other study, while reporting on the protocol (and steps to adapt the ICT application, previously reported as effective in HIC contexts to a specific LMIC context), has not yet as of the date of writing this EGM, published outcome results related to the reduction of IPV. Of the four reviews identified as eligible, two are better characterized as either a literature review or case study rather than as traditional systematic reviews reporting on impact outcomes with methodologically rigorous protocols. Authors' Conclusions: The evidence baseline for using ICT to prevent and/or respond to SGBV against women and children in LMIC is nascent. Promising areas for future study include: (1) how ICT can contribute changing gender and social norms related to SGBV and primary prevention; (2) mobile phone applications that promote safety and security; (3) mobile technology for the collection and analysis of survivors' experience with SGBV response services; and (4) digital tools that support the collection of forensic evidence for SGBV response and secondary prevention. Most striking is the paucity of eligible studies examining the use of ICT in connection with preventing or responding to SGBV against children. In light of the exponential increase in the use of ICT by children and adolescents, even in LMIC, greater attention should be given to examining how ICT can be used during adolescence to address gender norms that lead to SGBV. While there appears to be interest in using ICT for SGBV prevention and/or response in LMIC, other than several ad hoc studies, there is little evidence of if, and how effective these interventions are. Further inquiry should be made regarding if and how interventions proven effective in HIC can be adapted to LMIC contexts.